Challenging in frequent jacking force surge in rock pipe jacking project: A case study in Guanjingkou, China - Chao Li; Zuliang Zhong; Xinrong Liu; Yi Zhang; Nanyun Wang (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
Previous studies have demonstrated that the surge in jacking force during the Guanjingkou project is caused by the contact conditions of the debris bentonite slurry outside the pipe. Therefore, this paper further systematically investigates the influence of different debris slurry mass ratios (SLRs) and different particle size distributions (PSDs) on the pipe-rock friction characteristics using friction tests. The test results reveal that under the same PSD, an adequate amount of slurry (with an SLR of 1:4) consistently yields the lowest friction coefficient. When the SLR is between 1:2 and 1:3, the viscosity of the slurry reaches its peak, resulting in the highest friction coefficient. Additionally, when the PSD is 1:1:5 and 1:1:15, the friction coefficient is primarily governed by the plowing effect at the contact surface. When the PSD is 5:1:1 and 15:1:1, the friction coefficient is mainly controlled by the void ratio (VR) of debris. In the case of PSDs 1:5:1 and 1:15:1, the friction coefficient is jointly controlled by the adhesion effect of high-viscosity slurry and the plowing effect at the contact surface, and it gradually shifts towards being dominated by the VR as the amount of debris increases. Regardless of the SLRs and PSDs, the continuous deposition of debris and the injection of slurry incessantly exacerbate both the plowing and adhesion effects, creating a vicious cycle. This is the reason why the high-pressure water flushing method can not only fail to resolve the issue but also accelerate the occurrence of the surge in jacking force.